Biomimetic Cucurbitacin B-Polydopamine Nanoparticles for Synergistic Chemo-Photothermal Therapy of Breast Cancer - Leng, Junke; Dai, Xiaofeng; Cheng, Xiao; Zhou, Hao; Wang, Dong; Zhao, Jing; Ma, Kun; Cui, Changhao; Wang, Li; Guo, Zhaoming (Frontiers in Bioengineering and Biotechnology, 2022)
Breast cancer is the most common malignant tumor in women. Researchers have found that the combined use of multiple methods to treat tumors is a promising strategy. Here, we have developed a biomimetic nano-platform PDA@MB for tumor targeted photothermal therapy (PTT) combined with chemotherapy. The 4T1 cell membrane loaded with cucurbitacin B (CuB) was used to coat polydopamine (PDA) nanoparticles, which gave PDA@MB nanoparticles the ability to target tumors and escape immune cells from phagocytosis. PDA@MB showed excellent photothermal performance including high photothermal conversion efficiency and photostability, and exhibited outstanding in vitro PTT effect under NIR laser irradiation. The high temperature ruptured the PDA@MB membrane to release CuB, which changed the tumor hypoxic environment, down-regulated the FAK/MMP signaling pathway, and significantly inhibited the metastasis and proliferation of tumor cells. The results of in vivo experiments indicated that the tumor growth of the 4T1 mouse tumor model was significantly inhibited. Additionally, toxicity studies showed that PDA@MB had good biocompatibility and safety. In conclusion, this study provides a promising chemo-photothermal therapy (CPT) nano-platform for precise and effective breast cancer therapy.